Effect of Sthanika Chikitsa in the Management of Yonivyapad (AYUSHDHARA, 2025)
Disorders of the female genital tract or the vaginal disorders are on rise due to the current lifestyle and food habits. It is considered as an important public health problem worldwide particularly in developing countries. World Health Organization (WHO), globally has reported an estimation of 357 million new cases of reproductive tract infection annually. These disorders can be correlated to Yonivyapads in Ayurveda and are twenty in number. All the Ayurveda Acharyas have described in depth about these disorders, its Dindana, Samprapti. Lakshanas and Chikitsa that includes both the Sarvadaihika and Sthanika chikitsa. Sthanika chikitsa or the local therapeutic procedure encompasses the treatments such as Yoni lepana, Yoni prakshalana, Yoni poorana, Yoni dhoopana, Yoni Abhyanga, Yoni Varti, Yonidharana etc. in the management of Yononivyapads. Application of these local therapies are said to produce effective results based on the procedure, duration, indications, selection of drugs and the patients. Due to the higher tendency of absorption in the vagina and the female genital tract, these local therapies or the Sthanika chikitsa act on the absorption mechanism and hence produces the effect of the medicine on the tissue applied thereby helps in the reduction of the disorders. The present study attempts to evaluate the effect of all the Sthanika chikitsa explained in the Ayurvedic medicine.